Role of Sociodemographic Variables and the Mother's Active Behavior on Active Commuting to School in Children and Adolescents - Rodriguez-Rodriguez, Fernando; Solis-Urra, Patricio; Mota, Jorge; Aranda-Balboa, Maria Jesus; Barranco-Ruiz, Yaira; Chillon, Palma (Frontiers in Pediatrics, 2022)
The main objective of the current study was to analyze how parents’ sociodemographic characteristics, mode of commuting and physical activity (PA) act as indicators of active commuting to school (ACS) in their children and adolescents. A total of 684 paired parents (52.8% mothers) and their respective offspring (33.7% girls) were included. The participants self-reported their sociodemographic characteristics, mode of commuting, and PA. Logistic regression analyses were performed using a stepwise approach, including, as indicators, parental characteristics, mode of commuting and PA. The main outcome was child and adolescent ACS. The odds ratio (OR) and R2 of Nagelkerke were obtained for each step. Parental sociodemographic characteristics were greater indicators of child ACS than the parental mode of commuting and PA. In children, the greatest predictive variables of ACS explained 38% of the variance and were as follows: car availability (OR=0.24), father’s educational level (OR=0.47), mother’s educational level (OR=1.95), mother’s active commuting to work (OR=4.52) and mother’s salary/month (OR=0.67). In adolescents, the greatest predictive variables of ACS explained 40% of the variance and were as follows: socioeconomic level (OR=0.43) and father’s active commuting (OR=10.6). In conclusion, sociodemographic factors are better indicators of ACS than parents’ physical activity and active commuting to work.